Uji Briket Bioarang yang Diproses Menggunakan Arang Kotoran Sapi, Arang Kotoran Kambing dan Arang Kotoran Ayam dengan Penambahan Sekam Padi terhadap Kualitas yang Dihasilkan - Emilia Rafu Berek (JAS, 2019)
This research has been carried out in the Laboratory of the Faculty of Agriculture, University of Timor, East Nusa Tenggara Province which lasted for 2 months from 28 December 2018 to 28 February 2019. The purpose of this study was to determine the quality of bioarang briquettes processed using charcoal, cow dung, goat dung and chicken manure with the addition of rice husk. This study used a Completely Randomized Design (CRD) with 3 treatments and each treatment was repeated 5 times so that there were 15 experimental unit units. The composition of the three briquettes has the same type of mass (300 grams). As for the tested treatments consist of: (P0) = 80% Cow Manure + 10% rice husk + 10% starch, (P1) = 80% Goat Manure + rice husk 10% + 10% starch and (P2) = 80% Chicken Manure + 10% rice husk + 10% starch. Anova variance results showed that the parameters of water content and ash content did not show any significant difference between treatments while the combustion rate and heating value showed significant differences between the directions of treatment (P> 0.05). It was concluded that the best quality briquettes are produced by briquettes made from basic ingredients of cow dung with the addition of rice husk which produces water content (35.69%), ash content (19.72%) and heating value (3379 cal / g) while the rate of combustion the best is a goat manure briquette with a 10% rice husk mixture.